Electronic Cigarette using in Surabaya's Personal Vaporizer Community - Apsari Damayanti (Universitas Airlangga, 2017)
Electronic cigarette is devices capable of delivering nicotine in an aerosolized form. The number of electronic cigarette users is increasing. Data showed an Indonesia electronic cigarette user in 2010 to 2011 is 0,5%. This research was observasional decriptive study and used cross sectional design. This research was conducted to 31 Surabaya's Personal Vaporizer members. The dependent variable in this study was electronic cigarette using, while independent variable were the knowledge, accessibility and family factor. Data were analyzed by prevalens ratio. The result showed that using of electronic cigarette mostly suffered by respondent age 26 to 35 years old was equal to 54,8%, male (96,8%) and educational level was senior high school to university (100%), occupation was employee (71%), had a smoking history (93,6%), and using electronic cigarette for smoking cessation (80,6%). The analyzed with prevalens ratio showed that right knowlegde about electronic cigarette was a protective factor to being using electronic cigarette (PR=0,89), accessibility ≤ Rp 100.000 was a risk to being using electronic cigarette, and family was a protective factor to being using electronic cigarette (PR=0,95). From all variable which were studied, only accessibility that a risk factor with electronic cigarette using. Therefore, education about electronic cigarette haved to do and controlling toward electronic cigarette user needed to do.   Keywords : electronic cigarette, accessibility, community, knowledge, behavior